Generalized Equilibrium Problem with Mixed Relaxed Monotonicity - Haider Abbas Rizvi; Adem Kılıçman; Rais Ahmad (The Scientific World Journal)
We extend the concept of relaxed α-monotonicity to mixed relaxed α-β-monotonicity. The concept of mixed relaxed α-β-monotonicity is more general than many existing concepts of monotonicities. Finally, we apply this concept and well known KKM-theory to obtain the solution of generalized equilibrium problem.